Study Of Challenges In Implementation Of Schemes By Financial Institution In Gondia District With Regards To Agriculture Sector (Journal of Namibian Studies : History Politics Culture, 2023)
Even before the advent of the contemporary banking system, the finance has been a significant source of funding. However, its primary purpose is to serve as a source of funding for the agricultural industry. This research looks at the challenges and opportunities facing financial institutions in the Gondia District when it comes to funding the agriculture industry. The impact of money matters on farming in India is investigated here. Data was gathered using a descriptive technique, and interviews and questionnaires were used to get information from participants. Percentages and tables were used in the presentation and analysis of the data acquired. Chi-square was also used as an analytical tool. The research concluded that the actions of financial institutions have a major impact on agricultural funding. In addition, the study found that banks’ lack of funds is not the primary barrier to providing loans for the agricultural industry. Inadequate infrastructure for storing materials and the prevalence of outdated technology are two additional challenges. Despite these challenges, it is ecognized that the financial Institutions have many goods to offer for higher production in the agricultural sector of the nation, provided they are supervised well. There are a number of recommendations made as a result of the difficulties financial institutions have had in financing agriculture. These include providing more government and financial support to the agricultural sector to boost development and create an enabling environment. This analysis leads us to the conclusion that money is the “life wire” of the agriculture industry.